The Effect of Household Characteristics on Child Mortality in Uganda - Kabagenyi, Allen; Rutaremwa, Gideon (American Journal of Sociological Research, 2013)
The objective of this study was to establish the relationship between household characteristics and mortality among children under the ages of five in Uganda. Uganda in 2006experienced a high infant mortality rate of 76 deaths per 1000, far above the world’s average of 52 deaths /1000 live births. Of the infants that survive to the first birthday, 67 out of 1000 died before reaching their fifth birthday. In order to address this problem, the authors used survey data on 4,169 women respondents drawn from 14 districts of Uganda where the Uganda Ministry of Health intended to implement the Health Sector Strategic Plan II (2005/06 – 2009/10). Brass-type indirect techniques for mortality estimation were employed to establish the mortality rates. In addition, logistic regression analysis examined factors related with child mortality. Findings show wide mortality differentials by household type, place of residence, and household size. Mother’s education and children ever born were the two major variables highly associated with child mortality. The study concludes that household structure was not related to child mortality. There is need for adult literacy, secondary and above education for women and sensitization about the effects of large households and children ever born. Such studies provide insight into understanding the relationship between various household characteristics and child health outcomes.
Keywords: Household; Characteristics; Child; Mortality; Uganda